Novel silaproline (Sip)-incorporated close structural mimics of potent antidepressant peptide drug rapastinel (GLYX-13) - Madica, Krishnaprasad; Nadimpally, Krishna Chaitanya; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2017)
Rapastinel (GLYX-13) is a C-amidated tetrapeptide drug under clinical development for adjunctive treatment of major depressive disorder (MDD). Rapastinel features two consecutive proline residues centered at the peptide sequence (Thr-Pro-Pro-Thr-NH2), which are detrimental to its biological activity. In this communication, we report the synthesis of very close structural analogues of rapastinel comprising silaproline (Sip) as proline surrogate. By virtue of its enhanced lipophilicity and metabolic stability, Sip introduction in the native rapastinel sequence is expected to improve its pharmacokinetic profiles.

Rigid peptide scaffold-incorporated structural analogs of the potent antidepressant peptide drug rapastinel (GLYX-13) - Nadimpally, Krishna Chaitanya; Chakrapani, Aswathi; Prabhu, Priyanka J.; Madica, Krishnaprasad; Sanjayan, Gangadhar J. (Chemistryselect, 2017)
Rapastinel (GLYX-13) is a natural amidated tetrapeptide (Thr-Pro-Pro-Thr-NH2)endowed with strong antidepressant property. Rapastinel shows considerable promise for treating drug-resistant major depressive disorder (MDD), and is under clinical phase III development. Herein, we report the synthesis of a novel class of analogues of the potent antidepressant peptide drug rapastinel featuring rigid dipeptide scaffolds comprising proline (L/D) and amino thiophene carboxylates (Atc). Amino thiophene carboxylate is a conformationally constrained aromatic beta-amino acid, known to rigidify peptide backbones thereby limiting the conformational flexibility of peptides and improving proteolytic stability.

Dimedone-based rigid organic scaffold for organizing symmetrical helical peptide chains. - Madica, Krishnaprasad; Lakshmi, Jerripothula K.; Madhu, Suresh; Nadimpally, Krishna Chaitanya; Gonnade, Rajesh; Jagadeesh, Bharatam; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
We describe herein design, synthesis and conformational investigations of polypeptides attached on a rigid dimedone template. Two identical peptide chains are attached on a single carbon containing dimedone as a scaffold. Dimedone assists in controlling the secondary interactions through strong intramolecular helical C-12 and C-15 membered bifurcated hydrogen bonding on both the peptide chains along with propagating the helical architecture of the peptide chains attached. There exists a C-6 hydrogen bonding for the single stranded peptides attached to dimedone. Extensive structural investigations involving single crystal X-ray diffraction, solution-state NMR and CD studies of oligopeptides have been undertaken.
Keywords: dimedone; Helical; hydrogen bonding; Peptides; template